18F-FDG PET/CT can correct the clinical stages and predict pathological parameters before operation in cervical cancer. Issue 5 (May 2016) - Yang, Zhuo; Xu, WeiNa; Ma, YaNan; Liu, KuiRan; Li, Yan; Wang, DanBo
Abstract: Objectives: To evaluate the value of the positron emission tomography-computed tomography (PET/CT) imaging in correcting the clinical stages and predicting pathological parameters before operation in cervical cancer. Methods: Medical records of preoperative PET/CT from 113 patients with cervical cancer were retrospectively reviewed and compared with clinical examination and pathological parameters. Results: The accuracy of tumor staging by PET/CT was 94.7%. The sensitivity and specificity to diagnose lymph node (LN) metastasis were 53.8% and 95.0%, respectively, with 98.4% and 59.2% for deep cervical stromal invasion. The positive predictive value was 58.3% and 75.9%, and the negative predictive value was 94.1% and 96.7%. Using maximum standardized uptake value (SUVmax ) = 1.05 and metabolic tumor volume (MTV) of LN = 0.50 or MTV of cervical lesions = 11.60 as cut-off value to diagnose LN metastasis individually, we have found that the sensitivity and specificity for SUVmax, MTV of LN and cervical lesions were 53.8% and 94.0%, 46.2% and 94.0%, 88.9% and 73.0%, respectively. For deep cervical stromal invasion, with cervical lesions SUVmax  = 7.83 or MTV = 8.76 as cut-off value, the sensitivity and specificity were 92.2% and 57.1%, 75.0% and 76.2%, respectively. Conclusion: PET/CT stage preoperative cervical cancer more objectively and accurately compared to traditional staging system. The LN metastasis and deep cervical stromal invasion of cervical cancer could be well predicted before operation by PET/CT so that the doctors can choose individualized treatment options.